Chabaudstrongylus ninhae (Trichostrongylidae: Cooperiinae) and Oesophagostomum muntiacum (Chabertiidae: Oesophagostominae) in feral alien Reeves's muntjacs on Izu-Oshima Island, Tokyo, Japan. (2020) - Setsuda, A.; Kato, E.; Sakaguchi, S.; Tamemasa, S.; Ozawa, S.; Sato, H.
Abstract: The naturalization of alien Reeves's muntjacs ( Muntiacus reevesi ) on Izu-Oshima Island, Tokyo, Japan, has proceeded intensively over the last five decades. To clarify whether the gastrointestinal helminths of these animals were brought from their original endemic area or were newly acquired in Japan, 32 Reeves's muntjacs trapped on the island were parasitologically examined. In addition to Gongylonema pulchrum in the oesophagus (34.4% prevalence), Chabaudstrongylus ninhae (Dróżdż, 1967) (Trichostrongylidae: Cooperiinae) and Oesophagostomum muntiacum Jian, 1989 (Chabertiidae: Oesophagostominae) were prevalent in the small (28.1%) and large (46.9%) intestines, respectively. For the first time, these trichostrongylid or chabertiid worms were genetically characterized based on partial nucleotide sequences of the nuclear ribosomal RNA gene (rDNA) and mitochondrial DNA cytochrome c oxidase subunit 1 gene ( cox-1 ), and the phylogenetic relationships with other members of their family were explored. Since these two intestinal nematode species are inherent in muntjacs, this study demonstrates a new distribution of exotic helminth species in Japan in accordance with the naturalization of alien mammalian hosts. The molecular genetic data collected here could assist the taxonomic assessment of morphological variants in different Muntiacus spp. and/or of different geographical origins. Furthermore, our data may help to define the phylogenetic relationships among such isolates.